Chronic Hepatitis C Virus Infection and the Proinflammatory Effects of Injection Drug Use. (11th August 2016) - Markowitz, Martin; Deren, Sherry; Cleland, Charles; La Mar, Melissa; Silva, Evelyn; Batista, Pedro; St. Bernard, Leslie; Gettie, Natanya; Rodriguez, Kristina; Evering, Teresa H.; Lee, Haekyung; Mehandru, Saurabh
Abstract: Background. Chronic inflammation, as defined by persistent immune activation, is associated with adverse clinical outcomes. People who inject drugs (PWID) have evidence of persistent immune activation. Here, in a cohort of PWID with or without hepatitis C virus (HCV) infection, we sought to dissect out the contribution of chronic HCV infection (common in PWID) from the effects of injection drug use itself. Methods. Four groups of study volunteers were recruited: group 1 comprised active PWID; group 2, individuals who ceased injecting drugs 1–2 months before recruitment; group 3, individuals who ceased injecting drugs 3–4 months before recruitment; and group 4, healthy volunteers. Soluble and cell-associated markers of immune activation were quantified. Results. HCV-viremic PWID have elevated levels of immune activation when compared to healthy volunteers. Cessation of injection drug use results in a decline in immune activation in the absence of HCV viremia, while HCV-viremic individuals who previously were PWID continue to harbor elevated levels of immune activation, as defined by increased levels of soluble CD14 and tumor necrosis factor α and by the presence of CD38 + HLA-DR + CD4 + and CD8 + T cells. Conclusions. Immune activation, a well-defined surrogate of poor clinical outcome that is elevated in PWID, can regress to normal levels in former injection drug users who are HCV aviremic. Therefore, enhanced harm-reduction efforts should incorporate aggressive treatment of HCV infection. Clinical Trials Registration. NCT01831284.